2014
DOI: 10.1186/1475-2891-13-105
|View full text |Cite
|
Sign up to set email alerts
|

Stool fatty acid soaps, stool consistency and gastrointestinal tolerance in term infants fed infant formulas containing high sn-2 palmitate with or without oligofructose: a double-blind, randomized clinical trial

Abstract: BackgroundFormula-fed (FF) infants often have harder stools and higher stool concentrations of fatty acid soaps compared to breastfed infants. Feeding high sn-2 palmitate or the prebiotic oligofructose (OF) may soften stools, reduce stool soaps, and decrease fecal calcium loss.MethodsWe investigated the effect of high sn-2 palmitate alone and in combination with OF on stool palmitate soap, total soap and calcium concentrations, stool consistency, gastrointestinal (GI) tolerance, anthropometrics, and hydration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 30 publications
11
62
1
6
Order By: Relevance
“…30 , 33 Loss of LCSFAs as soaps, also leads to loss of energy. 34 Thus, the effect of sn-2 positioning of fatty acids in human milk and vegetable oil based formulas has been summarized in Fig. 5.…”
Section: Fat Structure and Composition In A Vegetable Oil-based Convementioning
confidence: 99%
See 1 more Smart Citation
“…30 , 33 Loss of LCSFAs as soaps, also leads to loss of energy. 34 Thus, the effect of sn-2 positioning of fatty acids in human milk and vegetable oil based formulas has been summarized in Fig. 5.…”
Section: Fat Structure and Composition In A Vegetable Oil-based Convementioning
confidence: 99%
“…42 Nowacki et al in 2014 suggested that high palmitic acid in sn-2 position lowered the formation of palmitic acid soaps. 43…”
Section: Tablementioning
confidence: 99%
“…На грудном вскармливании младенцы имеют более мягкий стул по сравнению с детьми, получающими стандартные формулы с небольшим количеством β-пальмитата [15][16][17]. С увеличением концентрации β-пальмитата в смеси за счет лучшего усвоения жирных кислот и увеличения доли усваиваемых ДЦ НЖК во 2-й позиции риск образования нерастворимых кальциевых мыл жирных кислот снижается с последующим улучшением консистенции, а именно мягкости стула без увеличения его общего объема [16].…”
Section: влияние βпальмитата на всасывание жирных кислот и консистенunclassified
“…С увеличением концентрации β-пальмитата в смеси за счет лучшего усвоения жирных кислот и увеличения доли усваиваемых ДЦ НЖК во 2-й позиции риск образования нерастворимых кальциевых мыл жирных кислот снижается с последующим улучшением консистенции, а именно мягкости стула без увеличения его общего объема [16]. Результаты двойного слепого плацебо-контролируемого исследования у здоровых доношенных детей свидетельствуют также о том, что этот эффект был более значимым при введении в состав смеси олигофруктозы [17,18].…”
Section: влияние βпальмитата на всасывание жирных кислот и консистенunclassified
See 1 more Smart Citation